EXOGAMI MARRIAGE BETWEEN SHARIFAH AND NON-SAYYID: STUDIES IN SOCIOLOGY AND FAMILY LAW - Aziz, Abdul; Subhan Nugraha, Iqbal (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2024)
This study aims to identify and analyze the factors that affect the obligation of equality of destiny in Sharifah marriage in East Jakarta. Equality of destiny is considered important in the Shari'ah marriage tradition, with several key factors influencing this view. The research method uses a qualitative approach with in-depth interviews with seven Habaib informants. Data were collected to explore their views on the obligation of equality of destiny and its implications in Sharifah marriage. The results of the study show that there are three main factors that underlie the equality of nasab: heredity, social factors, and madzhab teachings. First, descent is considered a mandatory tradition established by ancestors. Second, social factors reflect the negative consequences of marrying a child to an individual who is not equal to fate, such as insults and the absence of habaib. Third, the teachings of madzhab, especially from the Shafi'iyyah and Hanabilah groups, set strict standards regarding equality of descent. The discussion revealed that these factors play an important role in maintaining tradition, social status, and harmony in the Shariah community. This research provides in-depth insights into how equality of nasab affects the social structure and marriage traditions among the Habaibs.